Evaluation of the Age- and Sex-Related Changes of the Osteogenic Differentiation Potentials of Healthy Bone Marrow-Derived Mesenchymal Stem Cells - Hyun-Jin Lee; Hyuna Lee; Chae-Bin Na; In-Seok Song; Jae-Jun Ryu; Jun-Beom Park (Medicina, 2021)
Background andObjectives: Human bone marrow-derived mesenchymal stem cells (BMSCs) are promising sources for cell-based regenerative therapy. The purpose of the present study was to elucidate the roles of age and sex on the cellular viability and osteogenic potential of BMSCs cultured in osteogenic media. Materials and Methods: Human BMSCs were isolated and expanded from 3 age groups—20s, 30s, and 50s—from both sexes. The total number of aspirates was ten, and each subgroup had five for 20s (two females and three males), three for 30s (one female and two male), and two for 50s (one female and one male). Analyses of the cell morphology, the cell viability, the expression of the stem cell marker SSEA-4, the secretion of human vascular endothelial growth factor (VEGF), the expression of Runx2 and collagen I, the metabolic activity, and the formation of mineralization nodules were performed. Results: No significant differences were found in the cell viability of human BMSCs cultured in osteogenic media among the different age groups. There were no significant differences in the expression of SSEA among the age groups or between males and females. There were no significant differences in the secretion of human VEGF between males and females. No significant differences in Runx2 or collagen I expression were noted by age or gender. Moreover, no significant differences were shown in osteogenesis by alizarin red staining. Conclusions: The human BMSCs showed no age-related decreases in cellular viability or osteogenic differentiation potential.